2002
DOI: 10.1128/jcm.40.1.133-139.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Astrovirus Infection in Barcelona, Spain

Abstract: A 3-year study involving 2,347 gastroenteritis samples was conducted to determine the prevalence, time distribution, and medical significance of human astrovirus infection in Barcelona, Spain. The overall incidence of astrovirus was found to be 4.9%. Mixed infections with other enteric agents were detected in 17.2% of all astrovirus-positive samples. During the 3-year period, the highest astrovirus incidence was reported in the winter months, although infections also occurred in summer. The peak detection rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

45
182
13
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(249 citation statements)
references
References 35 publications
45
182
13
9
Order By: Relevance
“…In children from Goiânia city, it was observed that astrovirus infections occurred in all age groups, with a higher detection rate in children up to 24 months of age. These results reinforce a previous study conducted in the same area (Cardoso et al 2002) and are also in accordance with a study carried out by Guix et al (2002) in Spain. In contrast, a higher positivity rate was observed in children older than 36 months of age in Brasília city.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In children from Goiânia city, it was observed that astrovirus infections occurred in all age groups, with a higher detection rate in children up to 24 months of age. These results reinforce a previous study conducted in the same area (Cardoso et al 2002) and are also in accordance with a study carried out by Guix et al (2002) in Spain. In contrast, a higher positivity rate was observed in children older than 36 months of age in Brasília city.…”
Section: Discussionsupporting
confidence: 83%
“…The astroviruses are recognized as one of the most common cause of viral gastroenteritis in infants and young children in worldwide (Giordano et al 2001) and its seasonality is variable according to the geographic region (Naficy et al 2000, Guix et al 2002. The main symptom of the astrovirus infections is a watery and mild diarrhea, which generally results in mild diarrheic disease (Matsui & Greenberg 2001), although a recent study has described astrovirus infection related to severe dehydrating gastroenteritis among isolated Brazilian communities (Gabbay et al 2006).…”
mentioning
confidence: 99%
“…During this survey, an additional three other genotypes (HAstV-2, -4, -5) were also detected but at low frequency. HAstV-4 and HAstV-5 have been sporadically detected in different geographical areas, and are regarded as strains of minor epidemiological relevance [1,4]. On the other hand, HAstV-2 represented the second most prevalent type detected in this study and in 2009 it appeared to be more common than HAstV-1 in the area or Parma.…”
mentioning
confidence: 67%
“…Astroviruses (AstVs), family Astroviridae, are enteric viruses associated with gastroenteritis in young children in both developed and developing countries [1]. AstVs have a single-stranded positive-sense RNA genome containing three open reading frames (ORFs).…”
mentioning
confidence: 99%
“…La tabla 2 se realizó para determinar la procedencia y el año en el cual se obtuvo cada cepa y relacionarlo con el resultado del comportamiento filogenético por NJ. Cuando se evalúan los HAstV, se detectan prevalencias muy bajas que no alcanzan a elevar el porcentaje de las diarreas diagnosticadas en un tipo de poblaciones como la nuestra (13)(14)(15)(16)(17).…”
Section: Resultsunclassified